Culture Renovation - Oakes, Kevin (McGraw Hill-Ascent Audio, 2021)
Most business leaders understand the power of a dynamic, positive culture-but almost every effort to change culture fails. Why? The approach is often all wrong. Rather than attempt to "transform" a new culture from the ground up, leaders need to instead spearhead a culture renovation. In Culture Renovation, Kevin Oakes provides tangible, tactical insights drawn from a robust data set and informed by CEOs and HR leaders at many of the world's top companies. In this book you'll find everything you need to rebuild your corporate culture with care and expertise, including three phases and detailed action steps for architecting the change you want to see; practical insights and examples from T-Mobile, Microsoft, 3M, and other top companies; the traits of a healthy corporate culture; and proven talent practices to maintain your new culture for long-term success. Oakes identifies eighteen proven leadership actions for turning any culture into an agile, resilient, and innovative high-performance organization. You'll learn how to best understand the culture in place today and set a new cultural path for decades to come; develop a cocreation mindset; identify influencers and blockers; ferret out skeptics and non-believers; measure, monitor, and report progress; and implement "next practices" in talent strategies to sustain the renovation.